DIGITAL TRANSFORMATION IMPACT ON ENVIRONMENTAL AND ECONOMIC PERFORMANCE: THE MODERATING ROLE OF TECHNOLOGICAL TURBULENCE - Wati, Erna; Winna; Yopie, Santi (Global Financial Accounting Journal, 2025)
This study explores the link between digital transformation and sustainable performance, emphasizing economic and environmental outcomes while considering the moderating effect of technological turbulence. Data from 81 respondents reveal that digital transformation improves economic performance through dynamic capabilities like resource adaptation, process innovation, and agility. It also enhances environmental performance by promoting energy efficiency, waste reduction, and green innovations. However, advanced stages of digital transformation may face diminishing returns due to organizational inertia and the high resource demands of digital technologies. Technological turbulence amplifies both the opportunities and challenges, requiring companies in volatile environments to focus on adaptability and strategic alignment. The study highlights the importance of a phased, context-sensitive approach to digital transformation to avoid resource overuse and environmental harm. These findings offer practical insights for optimizing digital strategies to achieve long-term economic and environmental sustainability. Future research should address limitations such as sample size and context, while exploring additional moderating factors across diverse industries.